RURAL credit structure needs genuine revitalisation (2007)
The target for doubling of bank credit for agriculture in three years is being obviously met because of a dictate from the government but the quality of such lending will be weak and a large proportion will come back as non-performing assets. Without the expansion of the rural branch network by the financially strong and dominant public sector banks with staff appropriately qualified for dealing with agriculture and micro enterprises, the objective of a rapid credit expansion is sure to be stifled. These banks have to expand their network even as they co-opt cooperatives and other local agencies to supplement their banking business and undertake to expand their cedit base in the informal sector. - Reproduced.
Keywords: Agricultural credit